Agile : an executive guide : real results from IT budgets / Jamie Lynn Cooke. - Cooke, Jamie Lynn (IT Governance Publishing, 2011)
This guide will help you make realistic decisions on whether Agile methodologies are appropriate for your organisation; it also suggests ways of introducing, incorporating and leveraging these methodologies.